The Effect of Sharia Financial Inclusion on Poverty in Aceh - Risa, Hanna; Manzilati, Asfi; Trapsila, Aji Purba (Journal of Indonesian Applied Economics, 2025)
Purpose This study aims to analyze the effect of sharia financial inclusion on poverty in Aceh, the only province in Indonesia that mandates all financial institutions to operate based on Islamic principles yet has the highest poverty rate in Sumatra. Design/methodology/approach The study employs microdata from the 2023 National Socioeconomic Survey (Susenas), using a sample of 13,398 households across Aceh Province. A binary logistic regression model is applied to examine the relationship between access to sharia financial products and services including bank accounts, sharia financing, and digital financial services on household poverty status. Findings The findings reveal that households utilizing sharia financial products and services have lower odds of experiencing poverty than those without such access. However, the usage rate remains relatively low, particularly among rural households and those engaged in the agricultural sector, which serves as the primary livelihood for the majority of households in Aceh. Research limitations/implications This study is limited to formal financial inclusion indicators available in the Susenas dataset. Consequently, other dimensions of Islamic financial inclusion, including ZISWAF, are not captured. Future studies should incorporate these dimensions to provide a more comprehensive analysis. Originality/value This study contributes to the limited literature on the relationship between sharia financial inclusion and poverty, particularly studies employing household-level microdata.